Transmission network planning using genetic algorithm - Nguyễn Xuân Vinh; Hồ Văn Hiến (Journal of Technical Education Science, 2013)
One of important economic-technique problem in power systems is to determine the optimal structure of the transmission network to satisfy the objectives that load growth and the requirements of safe-economic electric distribution. This paper proposed an application of genetic algorithms (genetic algorithm-GA) to determine the optimize structure of transmission network to satisfaction meet load growth and the requirements of an electrical distribution secure and economy, with such constraints: power balance at the nodes, load capacity of the line, limited angle of the line voltage, the maximum number of lines installed last between two nodes. The accuracy of the algorithm was verified through simulation as well as comparions with other results of [2], [5], [6], [7], [8].